Design of a Monitoring System and Automatic Power Circuit Breaker in Flood Prone Areas Based on the Internet of Things - Ferdyanto; Wildan Hakim; Muhamad Alif Razi; Muhammad Raihan Fadhlurrahman (Faculty of Engineering, Universitas Brawijaya, 2025)
Flooding is a natural disaster that occurs due to overflowing water and can cause electrical short circuits in residential areas, endangering the safety of residents and damaging electronic devices. This study aims to design an automatic system for breaking and connecting electrical currents based on the Internet of Things (IoT) that is able to respond to water levels in real-time. The system uses an HC-SR04 ultrasonic sensor and an analog water level sensor connected to an ESP32 microcontroller. When the water reaches a certain limit, the ESP32 will activate the servo motor to cut off the electricity flow to the MCB and send a notification via Telegram. The method used is Research and Development (R&D), including hardware and software design, sensor integration, and system testing. The test results show that the system has a detection accuracy of 98% and is able to cut off or connect the current in less than 2 seconds. Notification delivery runs 100% on a stable network. This system is effective in increasing electrical safety during floods.